NMR methods for the estimating of the domain wall pinning force in cobalt - Gavasheli, T.A.; Mamniashvili, G.I.; Gegechkori, T.O. (Edelweiss Applied Science and Technology, 2024)
Two alternative NMR spin-echo methods under the influence of an additional magnetic video-pulse were applied to study pinning force in cobalt. The first one uses the action of a magnetic video-pulse on a two-pulse echo signal and the second one – the combined action of an RF and magnetic video-pulse, leading to the appearance of an edge single-pulse echo signal. The possibility of measuring the pinning force of domain walls in cobalt was comparatively studied by these methods. The data obtained also make it possible to modify some earlier obtained results on the effect of an additional magnetic video-pulse on the nuclear spin-echo signals in magnets, taking into the account of the pinning force of domain walls.